2019
DOI: 10.15835/nbha47411596
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Strategies of Structures that Enhance Invasion in Sicyos angulatus

Abstract: Sicyos angulatus may become an extremely dangerous invasive plant depending on its ability to naturalize and outcompete other species. To further understand the adaptive strategies of structures that could enhance its competitiveness, field surveys and experimental studies were conducted in plant communities where invasion may occur. The results showed that multistage branches of tendrils ensured that the plants could climb higher to strive for better photosynthetic opportunities. The single fleshy fruit of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…The high invasiveness is likely derived from its competitive ability of crowding out the neighboring plants (Zhao et al. 2019 ). Its vines can pull a crop to the ground, making crop harvesting nearly impossible, so it is problem to corn and soybean farmers (Esbenshade et al.…”
mentioning
confidence: 99%
“…The high invasiveness is likely derived from its competitive ability of crowding out the neighboring plants (Zhao et al. 2019 ). Its vines can pull a crop to the ground, making crop harvesting nearly impossible, so it is problem to corn and soybean farmers (Esbenshade et al.…”
mentioning
confidence: 99%
“…Moreover, Zhao et al (2019) noted the visitation of ants to male burcucumber flowers in the introduced region in China. Our study in the introduced region in Japan confirmed that ants ( Lasius sp., Oligomyrmex sp., and Pristomyrmex punctatus ) visited and fed on nectar from male and female burcucumber inflorescences in the afternoon in the NG population (Figure S2a).…”
Section: Discussionmentioning
confidence: 99%
“…Each flower is inconspicuous and whitish‐yellow‐green in color (Figure 1a). Male flowers are slightly larger than female flowers, with diameters of 6–10 and 4–6 mm, respectively (Zhao et al, 2019). In Japan, the flowering period extends from July to November, with no differences in floral morphology between flowers that bloom in the early, peak, or late season.…”
Section: Methodsmentioning
confidence: 99%
“…Vines of Cucurbitaceae are commonly cultivated as ornamental, edible, and medicinal plants [11,12]. Unfortunately, many of them easily escape from their cultivation sites and become established and invasive in new areas [13,14]. Successful invasion of alien vines of Cucurbitaceae can be explained by their fast growth and various methods of dispersal.…”
Section: Introductionmentioning
confidence: 99%